The extension of Technology Acceptance Model (TAM): effects of social media, facilitating conditions and perceived risk in online purchase in Saudi Arabia / Areeg Abdulghani Almowalad - Abdulghani Almowalad, Areeg (Institute of Graduate Studies, UiTM, 2018)
In Saudi Arabia, there is currently an active revolution not only in its physical and economy development, but also in the purchasing behaviour among Saudis. The world is observing massive change in people’s behaviour in communication and the influence technology has on it. This has led to numerous studies related to information technology and purchasing behaviour, in particular the reality of online purchasing in Saudi Arabia. As it involves technology, the Technology Acceptance Model (TAM) has been widely used in various studies in the attempt to understand people’s intention and actual behaviour online through the involvement of several external factors. This study is designed to examine the effects of ease of use, usefulness, enjoyment, and trust as the direct antecedent to intention, while social media, facilitating conditions and perceived risk are the moderating effects between intention and actual purchase to be able to advance the theories in TAM. This study aims to answer seven research questions by proving seven hypotheses involving seven relationships of dependent, independent as well as moderating variables…